Mutation Detection and Accurate Diagnosis of Extensively Drug-Resistant Tuberculosis: Report from a Tertiary Care Center in India - Ajbani, Kanchan (American Society for Microbiology, 2011)
We screened and spoligotyped 150 consecutive phenotypically confirmed extensively drug-resistant Mycobacterium tuberculosis (XDR-TB) isolates (January 2008 to March 2009) for rifampin, isoniazid, fluoroquinolone, and aminoglycoside resistance targeting rpoB, inhA, katG, gyrA, gyrB, and rrs. Mutations predominant among XDR-TB were S315T (katG) (100% of isolates), S531L (rpoB) (97% of isolates), D94G (gyrA) (53% of isolates), and A1401G (rrs) (71% of isolates). Spoligotyping revealed 62% of the isolates to be Beijing.